Maternal and child health nursing : care of the childbearing and childbearing family - Pillitteri, Adele (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
Adele Pillitteri aims to ensure that today's students have a technical understanding, without losing the importance of compassion in their role as a nurse. The text presents pediatrics and maternity as a continuum of knowledge, taking a holistic approach and viewing maternity and pediatric content as a family event. The text links theory closely with application that helps students gain a deeper understanding of content and be better prepared to practice in their careers."--Provided by publisher
A framework for maternal and child health nursing -- The childbearing and childrearing family -- Cultural diversity and maternal and child health nursing -- The childbearing and childrearing family in the community -- The nursing role in reproductive and sexual health -- Nursing care for the family in need of reproductive life planning -- The nursing role in genetic assessment and counseling -- Nursing care of the family having difficulty conceiving a child -- Nursing care of the growing fetus -- Nursing care related to psychological and physiological changes of pregnancy -- Nursing care related to assessment of a pregnant family -- Nursing care to promote fetal and maternal health -- The nursing role in promoting nutritional health during pregnancy -- Preparing a family for childbirth and parenting -- Nursing care of a family during labor and birth -- The nursing role in providing comfort during labor and birth -- Nursing care of a postpartal family -- Nursing care of a family with a newborn -- Nutritional needs of a newborn -- Nursing care of a family experiencing a pregnancy complication from a preexisting or newly acquired illness -- Nursing care of a family experiencing a sudden pregnancy complication -- Nursing care of a pregnant family with special needs -- Nursing care of a family experiencing a complication of labor or birth -- Nursing care of a family during a surgical intervention for birth -- Nursing care of a family experiencing a postpartum complication -- Nursing care of a family with a high-risk newborn -- Nursing care of the child born with a physical or developmental challenge. Principles of growth and development -- Nursing care of a family with an infant -- Nursing care of a family with a toddler -- Nursing care of a family with a preschool child -- Nursing care of a family with a school-age child -- Nursing care of a family with an adolescent -- Child health assessment -- Communication and teaching with children and families -- Nursing care of a family with an ill child -- Nursing care of a family when a child needs diagnostic or therapeutic modalities -- Nursing care of a family when a child needs medication administration or intravenous therapy -- Pain management in children -- Nursing care of a family when a child has a respiratory disorder -- Nursing care of a family when a child has a cardiovascular disorder -- Nursing care of a family when a child has an immune disorder -- Nursing care of a family when a child has an infectious disorder -- Nursing care of a family when a child has a hematologic disorder -- Nursing care of a family when a child has a gastrointestinal disorder -- Nursing care of a family when a child has a renal or urinary tract disorder -- Nursing care of a family when a child has a reproductive disorder -- Nursing care of a family when a child has an endocrine or metabolic disorder -- Nursing care of a family when a child has a neurologic disorder -- Nursing care of a family when a child has a vision or hearing disorder -- Nursing care of a family when a child has a musculoskeletal disorder -- Nursing care of a family when a child has an unintentional injury -- Nursing care of a family when a child has a malignancy -- Nursing care of a family when a child has a cognitive or mental health disorder -- Nursing care of a family in crisis: maltreatment and violence in the family -- Nursing care of a family when a child has a long-term or terminal illness
Includes index.
Keywords: MATERNAL-CHILD NURSING